2019
DOI: 10.15252/embj.2019102679
|View full text |Cite
|
Sign up to set email alerts
|

EGAD ! There is an ERAD doppelganger in the Golgi

Abstract: Disposal of membrane proteins in the late secretory pathway is thought to be exclusively facilitated by ESCRT‐dependent lysosomal degradation. In this issue of The EMBO Journal, Schmidt et al define a previously uncharacterized endosome and Golgi‐associated degradation (EGAD) pathway. This pathway, which has remarkable similarities to ERAD in the endoplasmic reticulum, operates in post‐ER organelles via the proteasome and contributes to lipid homeostasis in eukaryotic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…It has been shown that a specific set of proteasomes and their protein partners are associated with the ER, Golgi, and plasma membrane 48 , 49 . Based on the results obtained in Figures 3 and 4 , we decided to determine the co-fractionation of the proteasome with the ER and Golgi in the iodixanol gradient fractionation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that a specific set of proteasomes and their protein partners are associated with the ER, Golgi, and plasma membrane 48 , 49 . Based on the results obtained in Figures 3 and 4 , we decided to determine the co-fractionation of the proteasome with the ER and Golgi in the iodixanol gradient fractionation.…”
Section: Resultsmentioning
confidence: 99%
“…The potential proteasome 26S and 30S in Figure 3 and the location of the second peak of Golgi in Figure 5 A suggest that a large part of capped proteasome complexes (26S and 30S) are co-fractionated with the Golgi apparatus. It has recently been shown that the 26S proteasome complex is associated with the Golgi apparatus as part of Golgi Apparatus-Related Degradation, or GARD, which plays a critical role in the late secretory pathway in normal conditions 48 and various secretion-related pathologies 53 . Expectedly, the ERAD protein p97 54 co-fractionated with proteasome complexes present in enriched ER/Golgi compartments, while P47, pan 14-3-3, and Gankyrin were dominantly found in early fractions (fractions 1-6), which correspond to lighter forms of proteasome complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, other E3 ligases exist that show different specificity for substrates [64]. Similar to ERAD, an endosome and Golgi-related stress-responsive associated degradation pathway (EGAD) exists in the Golgi [4]. EGAD is implicated in several processes including changes in the size, subcellular localization and organization of the Golgi, thus impacting on cell fate and cellular pathways.…”
Section: Maintenance Of Early Secretory Pathway Homeostasis and Immentioning
confidence: 99%
“…ER-dependent protein quality control imposes a collaboration between protein synthesis and productive folding, ER-associated degradation (ERAD) [2] and ER homeostasis control (unfolded protein response; UPR) [3]. In addition, Golgi-dependent quality control mechanisms are necessary to monitor polypeptides maturation and post-translational modifications [4]. For instance, modifications such as N-linked glycosylation, which is critical for protein recognition and integral maturation, is initiated in the ER and completed in the Golgi.…”
Section: Introductionmentioning
confidence: 99%
“…Dsc3 contains a Ubl domain, and shares some similarities to the transmembrane and ubiquitin-like (Ubl) domain containing protein 1/2 (TMUB1/2). Ubx3 has a C-terminal UBX domain that can bind to Cdc48 18 , and is related to the FAS-associated factor 2 (FAF2/UBXD8).Overall, the subunit architecture of the Dsc complex resembles ubiquitin ligase complexes that function in ER associated degradation (ERAD) [19][20][21][22] .The Dsc complex can ubiquitinate ectopically expressed, non-native proteins at Golgi and endosomes, 16,23,24 . The Vld1-Dsc complex ubiquitinates native vacuolar membrane proteins (mainly lysosomal transmembrane transporters) 25,26 .…”
mentioning
confidence: 99%